The Varus Osteoarthritic Knee Has No Coronal Contractures in 90 Degrees of Flexion - McAuliffe, Michael J.; Roe, John; Garg, Gautam; Whitehouse, Sarah L.; Crawford, Ross (The Journal of Knee Surgery, 2017)
Medial and lateral coronal soft tissue laxity in 90 degrees of flexion in the varus osteoarthritic (OA) knee at the time of total knee arthroplasty (TKA) is unknown, meaning, key information as to how the flexion gap should be addressed by surgery is not available. The purpose of this study was to define the coronal plane medial and lateral laxity in 90 degrees of flexion in the end-stage OA knee. Computer assisted surgery (CAS) displays and direct joint observations were used to manipulate the knee to its neutral position in 90 degrees of flexion prior to any surgical releases. Laxity was measured as medial and lateral displacement from the neutral axis of the knee and compared with literature values for healthy subjects. The 72 knees examined had a mean varus deformity, measured in maximum extension, of −7.9 ± 3.1 degrees (−0.5 to −15 degrees). At 90 degrees of flexion, mean medial and lateral laxity as measured by displacement from the neutral axis of the knee was 3.8 ± 1.4 degrees and 4.7 ± 2 degrees respectively. This medial laxity was significantly greater −1.7 degrees (95% CI, −3.1 to −0.3 degrees) than that seen in healthy knees (p < 0.0001) whereas the measured lateral laxity displayed a nonsignificant difference compared with healthy knees. The mean difference in medial-lateral laxity was 1.5 ± 1.1 degrees. A medial-lateral difference of ≤2.5 degrees was present in 91.6% of knees. We found no evidence of contractures in the coronal plane tissue of the end-stage OA knee at the time of TKA. Absolute medial-lateral balance is not typical of the end-stage OA knee in 90 degrees of flexion with a small medial-lateral difference typically present. Careful examination of the soft tissues in flexion at the commencement of TKA may help guide surgery to optimize the coronal plane soft tissue envelope. Our findings would suggest that large releases during either a gap-balanced or a measured-resection TKA would not typically be necessary, and that releases that increase laxity in flexion may increase often already lax medial tissue or increase laxity within lateral tissues that typically already have physiological tension.
Keywords: varus; total knee arthroplasty; 90-degree flexion; coronal plane laxity; computer assisted